2019
DOI: 10.32572/guntad.502563
|View full text |Cite
|
Sign up to set email alerts
|

Sürdürülebilir Turizm Makalelerinin Bibliyometrik Analizi

Abstract: Çalışmada 2010-2017 yılları arasında sürdürülebilir turizm konusu ile ilgili uluslararası alan yazınında yayınlanan makalelerin belirli parametreler kapsamında incelenmesi amaçlanmaktadır. Çalışmada, makalenin yayınlandığı dergi, yayınlanma yılı, sayfa ve yazar sayıları gibi parametreler kullanılmıştır. Bu parametreler doğrultusunda Social Science Citation Index'den yararlanılmış; Journal of Sustainable Tourism, Sustainability gibi dergiler taranarak 288 adet makale değerlendirilmiştir. Makalelere ait parametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
2
0
8
Order By: Relevance
“…Additionally, research on health tourism (Temizkan et al, 2015), alternative tourism (Düşmezkalender and Metin, 2019), and sustainable tourism (Yeksan and Akbaba, 2019) has been evaluated with bibliometric analysis, providing insights into alternative tourism types beyond mass tourism and the fundamental concepts of tourism. Tayfun et al (2016) conducted a bibliometric analysis of 367 postgraduate theses on tourism published between 1985 and 2016, categorizing them based on certain characteristics.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Additionally, research on health tourism (Temizkan et al, 2015), alternative tourism (Düşmezkalender and Metin, 2019), and sustainable tourism (Yeksan and Akbaba, 2019) has been evaluated with bibliometric analysis, providing insights into alternative tourism types beyond mass tourism and the fundamental concepts of tourism. Tayfun et al (2016) conducted a bibliometric analysis of 367 postgraduate theses on tourism published between 1985 and 2016, categorizing them based on certain characteristics.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Güdü Demirbulat ve Tetik Dinç (2017) tarafından yapılan araştırmada 1987-2015 sürdürülebilir turizm konularını kapsayan lisansüstü tezler analiz edilmiştir. Sürdürülebilir turizm konusunda yayınlanan makaleleri konu olan bibliyometrik çalışmada ise 2010-2017 yılları arasında incelemeler yapılmıştır (Yeksan ve Akbaba, 2019).…”
Section: Turi̇zm Alaninda Bi̇bli̇yometri̇k çAlişmalarunclassified
“…Bibliyometrik analiz ile literatürdeki ilgili konu hakkında mevcut durum değerlendirmesinin yapılması ve akademik yayın kalitesinin artırılması hedeflenmektedir. Literatürde bibliyometrik analiz yönteminin kullanıldığı çok sayıda araştırma yer almaktadır (Çiçek ve Kozak, 2012;Yeksan ve Akbaba, 2019;Özkan ve Gül, 2019;Ece, 2007). Ancak ulusal literatürde kentsel tarım alanıyla ilgili yapılmış herhangi bir bibliyometrik analiz çalışmasına literatürde rastlanılmamıştır.…”
Section: Introductionunclassified
“…The bibliometric method is the mathematical and statistical analysis of published books, articles, papers, and journal academic studies (Pritchard, 1969;Diodato, 1994). The bibliometric method has been the subject of research in many fields (Çiçek and Kozak, 2012;Yeksan and Akbaba, 2019;Özkan and Gül, 2019;Ece, 2007). However, no bibliometric analysis study has been found in the urban agriculture literature.…”
Section: Introductionmentioning
confidence: 99%